2022
DOI: 10.3390/ijerph19074048
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Surgical Site Infection and Use of Antibiotics among Patients Who Underwent Caesarean Section and Herniorrhaphy at a Regional Referral Hospital, Sierra Leone

Abstract: Surgical site infections (SSIs) are common postoperative complications. Surgical antibiotic prophylaxis (SAP) can prevent the occurrence of SSIs if administered appropriately. We carried out a retrospective cohort study to determine the incidence of SSIs and assess whether SAP were administered according to WHO guidelines for Caesarean section (CS) and herniorrhaphy patients in Bo regional government hospital from November 2019 to October 2020. The analysis included 681 patients (599 CSs and 82 herniorrhaphies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 13 publications
2
18
2
Order By: Relevance
“…Conversely, the prevalence of SSIs found in our study was lower than what was found in similar studies with a prevalence of 10.9% in Tanzania [36], 11% in Ethiopia [37], 16.2% in Nigeria [38], 12.6% in Nepal [39] and 24.3% in Pakistan [40]. These results are not consistent with another study [41] which found that 7.5% of the CS deliveries had SSIs. This is presumably due to the long duration of prophylaxis [41].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Conversely, the prevalence of SSIs found in our study was lower than what was found in similar studies with a prevalence of 10.9% in Tanzania [36], 11% in Ethiopia [37], 16.2% in Nigeria [38], 12.6% in Nepal [39] and 24.3% in Pakistan [40]. These results are not consistent with another study [41] which found that 7.5% of the CS deliveries had SSIs. This is presumably due to the long duration of prophylaxis [41].…”
Section: Discussioncontrasting
confidence: 99%
“…These results are not consistent with another study [41] which found that 7.5% of the CS deliveries had SSIs. This is presumably due to the long duration of prophylaxis [41]. Some other studies have indicated that emergency CS deliveries have been linked to SSIs, due to highly urgent operations with fewer concerns about sterility and the absence of prophylactic antibiotics administered on time [31] [42] [43] [44].…”
Section: Discussioncontrasting
confidence: 97%
“…In keeping with our findings, a recently published study on antibiotic use among suspected and confirmed COVID-19 cases admitted to 35 COVID-19 hospitals in Sierra Leone also documented a high prevalence of antibiotic use, as over half of the patients admitted to these centres received an antibiotic 15. Several other studies conducted in the general patient population including surgical patients have also demonstrated a high prevalence of antibiotic use 22 30–32. Additionally, a multicentre PPS on antibiotic use in Ethiopian hospitals that involved a review of over 1800 patient records documented a high prevalence (63.8%) of antibiotic use 33.…”
Section: Discussionsupporting
confidence: 88%
“…[36] Similar practices have been reported from other LMICs, indicating the use of prolonged prophylactic antibiotics for Csection may be widespread, despite evidence showing no benefit from multiple doses of antibiotics. [37][38][39][40] This contrasts with practices in high-resource contexts, such as the U.S., where multiple doses of antibiotics is rare. [41,42] Although the analysis conducted here was exploratory, prior hospitalization was consistently associated with increased risk for maternal ESBL/CRO colonization, implicating the role of healthcare settings in the propagation of AMR.…”
Section: Discussionmentioning
confidence: 98%